2022
DOI: 10.1186/s12885-022-09309-6
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy versus chemoradiotherapy for FIGO stages IB1 and IIA1 cervical squamous cancer patients with lymphovascular space invasion: a retrospective study

Abstract: Purpose To evaluate the impact of different adjuvant therapy on IB1 and IIA1 stage cervical squamous cell cancer patients with lymphovascular space invasion. It also aimed to analyze the relationship between lymphovascular space invasion and other clinical pathological characteristics on IB1 and IIA1 stage cervical squamous cell cancer patients. Methods This retrospective observational study collected data of FIGO stages IB1 and IIA1 squamous cervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…These include urinary disturbances, lower-limb lymphedema, bowel obstruction, sexual and ovarian dysfunction, and mental health issues stemming from these chronic conditions ( 6 8 ). Given these complications, there has been a global shift towards exploring adjuvant chemotherapy as an alternative, with promising results reported ( 6 , 7 , 9 , 10 ). A notable randomized non-inferiority multicenter trial showed no significant difference in 3-year progression-free survival rates, which were 91.9% in both the adjuvant chemotherapy and concurrent chemoradiation therapy (CCRT) groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include urinary disturbances, lower-limb lymphedema, bowel obstruction, sexual and ovarian dysfunction, and mental health issues stemming from these chronic conditions ( 6 8 ). Given these complications, there has been a global shift towards exploring adjuvant chemotherapy as an alternative, with promising results reported ( 6 , 7 , 9 , 10 ). A notable randomized non-inferiority multicenter trial showed no significant difference in 3-year progression-free survival rates, which were 91.9% in both the adjuvant chemotherapy and concurrent chemoradiation therapy (CCRT) groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, irradiation or concurrent chemoradiation following radical surgery can lead to adverse events, including urinary disturbance, lower-limb lymphedema, bowel obstruction, sexual dysfunction, ovarian dysfunction, and mental health issues associated with these lasting adverse effects ( 6 8 ). Given these concerns, efforts have been made globally to introduce postoperative adjuvant chemotherapy for patients at intermediate or high risk of recurrence ( 6 , 7 , 9 , 10 ). However, the current evidence supporting chemotherapy as postoperative adjuvant therapy is limited, and careful consideration is warranted when determining its suitability.…”
Section: Introductionmentioning
confidence: 99%
“…However, the combination of radical hysterectomy and whole-pelvic irradiation or chemoradiation is linked with an increased occurrence of complications such as lower-limb lymphedema, urinary disturbance, bowel obstruction, sexual dysfunction, and mental issues related to those lasting issues (4)(5)(6). Chemotherapy has been reported as an effective post-surgical adjuvant therapy for patients with intermediate-and high-risk stage IB-IIB cervical cancer (7)(8)(9). For these reasons, chemotherapy has been increasingly chosen as post-surgical adjuvant therapy in clinical practice (10,11).…”
Section: Introductionmentioning
confidence: 99%
“… 10 Since knowledge of the prognosis of metastatic number and sites is crucial for pre-treatment evaluation, our study aimed to analyze the impact of metastases in different systems, such as lymph node (LN) and hematogenous (including lung, liver, bone and other organs) systems, and in specific locations on the prognosis of mCC patients. In addition, previous studies found that definitive pelvic radiotherapy and chemotherapy were associated with significantly longer survival compared with chemotherapy alone for cervical cancer patients, 8 , 11 , 12 but the effect of the appropriate timing of chemoradiotherapy (CRT) in patients with mCC has not been well studied. Until now, many studies related to mCC have contained patients with both synchronous and recurrent metastatic diseases.…”
Section: Introductionmentioning
confidence: 99%